Assessment of sleep Quality among cancer patients undergoing chemotherapy - عساف ليلا; سوسن غزال; نادر عبدالله (Latakia University Journal -Medical Sciences Series, 2024)
The current descriptive study aimed to evaluate the sleep quality of cancer patients undergoing chemotherapy. The study included 60 patients at the Chemotherapy and Radiotherapy Treatment Center at Tishreen University Hospital in Lattakia. They were selected using convenience sampling, and data was collected using the Pittsburgh Sleep Quality Index. The study found that the majority of cancer patients undergoing chemotherapy had somewhat poor sleep quality. They took between half an hour to an hour to fall asleep after getting into bed, and their sleep duration ranged from five to six hours. Their sleep efficiency was between 75-84%, indicating a significant sleep disturbance. They needed sleep medication once or twice a week, and they experienced mild disruption in daily activities over the past month. More than three-quarters of them had poor sleep quality. There were no significant differences in sleep quality attributed to their demographic characteristics. The study recommended the necessity of scheduling patients’ need for sleep within the treatment plan, designing programs to improve their sleep, and conducting a similar study on a larger sample. .